Mediating effect of self-coping mechanisms on associations between financial practices and financial security of female-headed households - Ahmad, Siti Yuliandi; Sabri, Mohamad Fazli; Abdul Rahim @ Abdul Wahab, Husniyah; Osman, Syuhaily (Malaysian Consumer and Family Economics Association, 2016)
Coping process involves contingency actions of individual to alter their cognitive and behaviour to cope with stress encountering events in life. Self-coping mechanisms were examined further as mediating effect between financial practices and financial security among female-headed households in Malaysia. A model was then constructed based on Characteristics Theory, Cognitive of Stress and Coping Theory. A multi-stage random sampling was executed and a self-administered survey was executed to collect data from 600 respondents from six single mother associations at every zone in Malaysia. A structural equation modelling using AMOS software was used to examine mediating effect of self-coping mechanisms in a relationship between financial practices and financial security of female-headed households in Malaysia. The findings support that a significant relationship exists between indirect and mediating models. The study revealed that there is a partial mediating effect of self-coping mechanisms between financial practices and financial security. The role of self-coping mechanisms is crucial to grasp a better understanding of how financial practices and financial security are related to improving the living standards of female-headed households. Implications and limitations of the study are dissussed further.